Synthesis of New Heterocyclic Compounds Derived from Anthrone and Evaluation of Their Biological Activity (Baghdad Science Journal, 2008)
In this research, Schiff bases derived from the reaction of anthrone with different heterocyclic amines have been described. The resulted Schiff base compounds were reacted with various nucleophiles in order to obtain new heterocyclic derivatives. Chemical structures of all products were confirmed by IR, 1H-, 13C-NMR spectral data and elemental analysis. All synthesized compounds were in vitro tested against a standard strain of pathogenic microorganism including Gram +ve bacteria (Staphylococcus aureus), Gram –ve bacteria (Escherichia coli), and fungi (Candida albicans).